EFFECT OF INTEGRATED NUTRIENT MANAGEMENT ON GROWTH, YIELD AND QUALITY OF PIGEONPEA ( ALITY OF PIGEONPEA (CAJANAS CAJAN L. MILLSP.) CV. PUSA 9. . PUSA 9. . PUSA 9. - SAHAY, ANISH; PRATAP, TEJ; SHEKHER SINGH, SHASHANK (The Bioscan, 2016)
An experiment was conducted during 2008-09 at Agricultural Research Farm, Department of Agronomy, Institute of Agricultural Sciences, Banaras Hindu University, Varansi, (India) to study the effect of Integrated nutrient management on growth, yield and quality of pigeonpea cv. Pusa 9. The experiment was laid out in randomized block design replicated trice with eight treatments viz, T1=50% RDF, T2=100% RDF, T3=50% RDF+5tFYM, T4=50% RDF+5tFYM+Rh, T5=50%RDF+Rh+PSB, T6=100%RDF+5t FYM, T7=100% RDF+5tFYM+Rh+PSB, T8=100%RDF+Rh+PSB. The growth attributes like plant height, numbers of branches, and dry matter accumulation per plant were increased progressively with increasing fertility levels. The maximum grain yield (1837) and stalk Yield (553 kg /ha) was obtained with the application of 100%RDF+5t FYM+Rh+PSB to pigeonpea. The quality attributes (NPK and protein content) of pigeonpea was significantly increased with fertility levels and maximum reported with 100%RDF+5tFYM+Rh+PSBdifferent fertility levels, 100%RDF+5tFYM+Rh+PSB was found more remunerative than that of other treatments. From this study it can be concluded that the application of 100%RDF+5tFYM+Rh+PSB among different fertility levels plants showed favourable growth and quality characters with improved yields attributes leads higher grain yield.